2011
DOI: 10.5653/cerm.2011.38.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Age specific serum anti-Müllerian hormone levels in 1,298 Korean women with regular menstruation

Abstract: ObjectiveTo determine the age specific serum anti-Müllerian hormone (AMH) reference values in Korean women with regular menstruation.MethodsBetween May, 2010 and January, 2011, the serum AMH levels were evaluated in a total of 1,298 women who have regular menstrual cycles aged between 20 and 50 years. Women were classified into 6 categories by age: 20-31 years, 32-34 years, 35-37 years, 38-40 years, 41-43 years, above 43 years. Measurement of serum AMH was measured by commercial enzyme-linked immunoassay.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 15 publications
3
28
1
3
Order By: Relevance
“…The distribution of AMH concentrations in women with PCOS was quite different from that in women with regular menstruation, as has been previously reported by Yoo et al [10]. The mean serum AMH levels of 1,298 women (mean age, 34.4±0.1 year) with regular menstruation was 3.6±0.1 ng/mL and decreased with age (Figure 1A).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The distribution of AMH concentrations in women with PCOS was quite different from that in women with regular menstruation, as has been previously reported by Yoo et al [10]. The mean serum AMH levels of 1,298 women (mean age, 34.4±0.1 year) with regular menstruation was 3.6±0.1 ng/mL and decreased with age (Figure 1A).…”
Section: Resultssupporting
confidence: 56%
“…(A) In women with regular menstruation (Adapted from Yoo et al Clin Exp Reprod Med 2011;38:93-7 [10]). (B) In women with PCOS (in present study).…”
Section: Figurementioning
confidence: 99%
“…Yoo et al19 reported that the AMH levels are significantly correlated with the OV in Korean women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…19 The AMH has been studied in different populations. 13,[20][21][22][23] It is known that AMH levels are not altered in women using hormonal contraceptives. 24 Some studies have evaluated AMH levels in patients with cancer and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%